2008
DOI: 10.1111/j.1939-1676.2008.0160.x
|View full text |Cite
|
Sign up to set email alerts
|

Lawsonia intracellularisInfection in Horses: 2005–2007

Abstract: Background: Lawsonia intracellularis is an emerging equine pathogen that is a cause of equine proliferative enteropathy (EPE).Objective: To describe the signalment, month of presentation, common clinical signs, clinicopathologic values, diagnostic tests used, antimicrobial use, and survival status in horses affected with EPE; to evaluate how affected horses sold at public auction as yearlings; and to determine results of fecal polymerase chain reaction (PCR) and serum immunoperoxidase monolayer assay (IPMA) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
111
3
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(128 citation statements)
references
References 17 publications
4
111
3
10
Order By: Relevance
“…Since the 1990s, it has been endemic in pigs and one of the most economically important diseases in the swine industry [4]. In the last decade, the disease also has been frequently reported in weanling foals worldwide, and now is described as an emerging disease in the horse population [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, it has been endemic in pigs and one of the most economically important diseases in the swine industry [4]. In the last decade, the disease also has been frequently reported in weanling foals worldwide, and now is described as an emerging disease in the horse population [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The ages of affected animals ranged from a few days to 21 months of age, although diarrhea associated with hypoproteinemia and submandibular edema had been observed more frequently in foals 3 to 6 months old, an age group in which animals are more susceptible to and affected by L. intracellularis (Pusterla et al 2010, Vannucci et al 2012). This predisposition is most likely associated with the decline of maternal antibodies (Pusterla et al 2008a), as well as stressors such as weaning, moving to new paddocks and barns, deworming and/ or vaccination programs and/or early conditioning programs (Frazer 2008), which were performed at this farm.…”
Section: Discussionmentioning
confidence: 99%
“…However, the first serum dilution used by that author was 1:30, while serological tests in our lab were 1:60, as this dilution showed the least nonspecific labeling. Epidemiological investigations on farms with clinical cases indicate that 10-65% of healthy adult horses and foals are seropositive for L. intracellularis (Frazer 2008, Pusterla et al 2009). The percentage of positive animals ranged from 3.57% to 16.67% in Minas Gerais herds, while the properties had no cases of clinical disease, which justifies lower rates of seropositive (Guimarães-Ladeira et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A recent large-scale study showed that only 80% of foals with presumptive diagnosis of EPE also had a positive serum titer against L. intracellularis by IPMA. 2 One must keep in mind that serologic and molecular tests will never achieve 100% accuracy in diagnosing EPE antemortem. It is rather the integration of clinical, clinicopathologic, sonographic, serologic, and molecular results that will support or rule out an EPE diagnosis.…”
mentioning
confidence: 99%
“…PCR appears to reliably demonstrate L. intracellularis in the feces of clinically affected horses early in the course of the disease. 2 As an alternative sample type to feces, rectal swabs are routinely used for the PCR detection of L. intracellularis in pigs because of the ease of collection. The purpose of the current study was to compare the molecular detection rate of L. intracellularis between feces and rectal swabs collected from foals with suspected EPE.…”
mentioning
confidence: 99%